Port rail connectivity and agricultural production: Evidence from a large sample of farmers in Ethiopia - Atsushi Iimi; Haileysus Adamtei; James Markland; Eyasu Tsehaye (Journal of Applied Economics, 2019)
Agriculture important in Africa, employing a large share of the labor force and earning foreign exchange. Transport connectivity has long been a crucial constraint in the region. In theory, railways have the advantage of shipping bulky freight, such as fertilizer, at low costs. However, in many African countries, railways were in virtual bankruptcy in the 1990s. Using a large sample of data comprised of more than 190,000 households over eight years in Ethiopia, the paper estimates the impacts of rail transport on agricultural production. The paper takes advantage of the historical event that a major rail line connecting the country to Port Djibouti was abandoned during the 2000s. With the fixed effects and instrumental variable techniques combined, an agricultural production function is estimated. It is found that deteriorated transport accessibility to the port had a significantly negative impact. The use of fertilizer particularly decreased with increased transport costs.
Keywords: C23; C26; Q12; R40; 330; Agriculture production; transport infrastructure